CoSMIC: A hybrid approach for large-scale, high-resolution microbial profiling of novel niches - Maor Knafo; Shahar Rezenman; Tal Idan; Michael Elgart; Shlomi Dagan; Vered Zavaro; Ziv Reich; Ruti Kapon; Dagan Sade; Noam Shental (PLoS ONE, 2026)
Standard microbial profiling based on 16S rRNA (16S) sequencing suffers from a lack of primer universality, primer biases, and often yields low resolution. We introduce ‘Comprehensive Small Ribosomal Subunit Mapping and Identification of Communities’ (CoSMIC), addressing these challenges, especially in unexplored niches. CoSMIC begins with long-read sequencing of the full-length 16S gene, amplified by generic Locked Nucleic Acid primers over pooled samples, thus augmenting reference databases with novel niche-specific gene sequences. Subsequently, CoSMIC amplifies multiple non-consecutive variable regions along the gene, followed by short-read sequencing of each sample. Data from the different regions are integrated using the SMURF framework, alleviating primer biases and providing de facto full gene resolution. Using a mock community, CoSMIC identified full-length 16S genes with significantly higher specificity and sensitivity while dramatically increasing resolution compared to standard methods. Evaluating CoSMIC across environmental samples yielded higher accuracy and unparalleled resolution at a fraction of the cost of standard long-read sequencing per sample while allowing the detection of thousands of novel full-length 16S sequences.